PENGANTAR ASUHAN SPIRITUAL DALAM KONTEKS PERAWATAN PALIATIF BAGI MAHASISWA KEPERAWATAN DI INDONESIA [INTRODUCTION OF SPIRITUAL CARE IN THE CONTEXT OF PALLIATIVE CARE TO NURSING STUDENTS IN INDONESIA] - Juniarta Juniarta; Ni Gusti Ayu Eka; Ineke Patrisia; Yenni Ferawati Sitanggang; Dwi Yulianto Nugroho (Jurnal Sinergitas PKM & CSR, 2020)
Spiritual care is an important component in providing holistic nursing care to both individuals and families. Therefore, nurses need to have knowledge and skills to recognize and address patients’ spiritual needs. Unfortunately, the spiritual aspect in health care is often neglected. Spiritual care in health care has started to be taught in nursing schools, specifically in Universitas Pelita Harapan, in which spiritual care is one of the core subjects that is taught by a faculty member who went through a training in spiritual care. Realizing that spiritual care is not necessarily included in nursing curricula in most nursing institutions in Indonesia, a webinar on spiritual care was conducted, especially in the context of palliative care. The purpose of this Community Service is to inform spiritual care in the context of palliative care to nursing students throughout Indonesia. The webinar was held on August 7, 2020 which was attended by 202 participants from various regions in Indonesia. The method used was lecture and question and answer. Evaluation was done by giving pre- and post-tests to participants. Participants’ feedback was obtained at the end of the webinar. The implementation of this webinar was proven to provide additional knowledge to nursing students who participated, indicated by an increase in the average pre-test and post-test scores by 21 points. BAHASA INDONESIA ABSTRACT: Asuhan spiritual merupakan komponen penting di dalam pemberian asuhan keperawatan yang holistik baik kepada individu maupun keluarga. Oleh karenanya, perawat perlu memiliki pengetahuan dan keterampilan untuk mengenali dan memenuhi kebutuhan spiritual pasien. Sayangnya, aspek spiritual dalam pelayanan kesehatan seringkali diabaikan. Pembelajaran tentang spiritualitas di Fakultas Keperawatan juga sudah mulai diperkenalkan, khususnya di Universitas Pelita Harapan, asuhan spiritual menjadi mata kuliah dengan pengajar yang telah mengikuti pelatihan asuhan spiritual. Menyadari bahwa asuhan spiritual belum tentu termasuk di dalam pengajaran di kebanyakan institusi keperawatan yang ada di Indonesia, maka dilaksanakan sosialisasi atau pengenalan melalui webinar mengenai asuhan spiritual, khususnya dalam konteks perawatan paliatif. Tujuan dari kegiatan Pengabdian kepada Masyarakat ini adalah untuk memberikan pengetahuan tentang asuhan spiritual dalam konteks perawatan paliatif kepada mahasiswa keperawatan di seluruh Indonesia. Webinar tersebut dilaksanakan pada 7 Agustus 2020 yang dihadiri oleh 202 orang peserta dari berbagai wilayah di Indonesia. Metode yang dilakukan dalam kegiatan ini adalah dalam bentuk ceramah dan diskusi tanya jawab. Evaluasi kegiatan dilakukan dengan memberikan pre- dan post-tes kepada peserta dan juga evaluasi kegiatan. Pelaksanaan webinar ini terbukti memberikan tambahan pengetahuan kepada mahasiswa keperawatan yang mengikuti ditunjukkan dengan peningkatan hasil rata-rata skor pre-test dan post-test sebesar 21 poin.